1997
DOI: 10.1007/bf02740621
|View full text |Cite
|
Sign up to set email alerts
|

The cellular and molecular basis of peripheral nerve regeneration

Abstract: Functional recovery from peripheral nerve injury and repair depends on a multitude of factors, both intrinsic and extrinsic to neurons. Neuronal survival after axotomy is a prerequisite for regeneration and is facilitated by an array of trophic factors from multiple sources, including neurotrophins, neuropoietic cytokines, insulin-like growth factors (IGFs), and glial-cell-line-derived neurotrophic factors (GDNFs). Axotomized neurons must switch from a transmitting mode to a growth mode and express growth-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
748
1
37

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,081 publications
(804 citation statements)
references
References 494 publications
18
748
1
37
Order By: Relevance
“…This indicated that axons distal to the suture remain capable of transporting tracers for a short time and that the dye may cross the suture and reach the DRG provided that the distal nerve remains in contact with its proximal stump. This is in accordance with previous reports, which described retrograde transport (Nitta et al, 1999) and excitability (Fu and Gordon, 1997) in the distal part of sectioned axons for a short period after transection. To avoid this "crossing" phenomenon, we waited three days after the nerve lesion and repair before we applied the tracers.…”
Section: Discussionsupporting
confidence: 94%
“…This indicated that axons distal to the suture remain capable of transporting tracers for a short time and that the dye may cross the suture and reach the DRG provided that the distal nerve remains in contact with its proximal stump. This is in accordance with previous reports, which described retrograde transport (Nitta et al, 1999) and excitability (Fu and Gordon, 1997) in the distal part of sectioned axons for a short period after transection. To avoid this "crossing" phenomenon, we waited three days after the nerve lesion and repair before we applied the tracers.…”
Section: Discussionsupporting
confidence: 94%
“…These varying results may to some extent be due to counting problems, but also to age, postoperative survival time, and proximity of lesion (see Lowrie and VrbovĂĄ, 1992;Snider et al, 1992;Fu and Gordon, 1997). By analogy to findings in the DRGs (Ygge and Aldskogius, 1984;Arvidsson et al, 1986;Groves et al, 1997), an increased amount of neuronal disappearence in the motor columns could take place if very long survival times were studied.…”
Section: Labelling With the First Tracer: Neuronal Death Versus Tracementioning
confidence: 95%
“…Nerve transection triggers a set of changes in the nerve stump distal to the injury that are collectively referred to as Wallerian degeneration (reviewed in Chen et al, 2007;Fu and Gordon, 1997;Raivich and Makwana, 2007;Scherer and Salzer, 2001;Stoll et al, 2002;Vargas and Barres, 2007). The major events are: axon death, invasion of blood-borne macrophages, collapse of myelin sheaths together with ingestion and breakdown of the myelin material, a transient phase of Schwann cell proliferation, and a reversal of molecular expression from that characteristic of mature myelinating and nonmyelinating cells back to one that resembles the immature state.…”
Section: Schwann Cell Dedifferentiation During Wallerian Degenerationmentioning
confidence: 99%